DETECTION OF TOXOPLASMOSIS AND SOME RISK FACTORS WITH THE INFECTION RATE IN LOCAL AND SHAMI GOATS - E.H. Madi,; F.R. Al-Samarai,; Y. M. A. Maaeni,; A.M. Abdel-Ghany, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to evaluate detection of T. gondii in blood DNA based on the B1 gene and serologically, also to investigate the effect of some risk factors (sex, ages, breeds and flocks). A total of 190 goats were included. The blood samples were obtained from the jugular vein and subjected to nested PCR (nPCR) and Elisa for detection of T. gondii. The results obtained that the prevalence was 24.21% by nPCR and 46.31% by ELISA with significant differences. The degree of agreement between nPCR and ELISA was a slight (Kappa=0.212).  The sensitivity and specificity of ELISA was 67.39 and 60.42 respectively. According to results of nPCR, there was a significant difference between sex, with a higher infection rate in males (40.42%) than females (18.88%). Males are more at risk to infection than that of female (The crude odds ratio (COR)=2.91, (95% CI 1.41-5.97) and adjusted odds ratio (AOR)=4.66, (95% CI 2.01-10.79). The infection rate in the Al-Dibuni flock (36.36%) was significantly higher than that of Abu-Gharib (19.25%). The goats in Al-Dibuni are more at risk to infection than that in Abu-Ghraib flock COR=2.39, (95%CI 1.19-4.80) and AOR=2.31, (95%CI 0.97-5.50).